Miesto bendrasis planas ir ekspertiniai vertinimai - Bardauskienė, Dalia (Journal of Architecture and Urbanism, 2007)
City master plan and expert assessmentsAfter the restoration of independence Lithuanian cities underwent big urban transformations which frequently took place without any clear strategy and master plans. Attention to urban planning intensified after Lithuania’s accession to the European Union. General planning works revealed trends of the planning system of cities and Lithuanian territories on the whole, but they did not give a proper answer to what extent the system complies with sustainable development targets, values of society‘s feeling and thinking.In this situation the second Master Plan of Vilnius City was drawn after the restoration of independence. Planning methods based on the results of expert evaluations and public process enabled to substantiate the solutions: to determine internal and external factors of urban development, transformations of urban structures, values of society. Compatibility of expert opinions verified by applying mathematical methods demonstrated high compatibility of the results of expert polls on Vilnius City Master Plan.A conclusion is made that Vilnius City Master Plan till 2015 reflects the interests and values of all the citizens and provides prerequisites for sustainable development. Successful implementation greatly depends on external factors, including solution of the problems of territory planning system and internal factors the key of which is reduction of differences between the city centre and outskirts. It is revealed that public rights to participate in the formation of cities are not adequate to knowledge and contribution to the implementation.Article in Lithuanian.Santrauka. Po nepriklausomybės atkūrimo Lietuvos miestai pergyveno dideles urbanistines transformacijas, kurios dažnai vyko be aiškios strategijos ir bendrųjų planų. Lietuvai tapus Europos Sąjungos nare dėmesys miestų planavimui suaktyvėjo. Bendrojo planavimo darbai atskleidė miestų, o kartu ir Lietuvos teritorijų planavimo sistemos raidos tendencijas, tačiau nedavė pamatuoto atsakymo, ar ji atitinka darniosios plėtros tikslus, visuomenės nuostatas ir vertybes. Vilniaus bendrojo planavimo pavyzdžiu nagrinėjamos aktualios Lietuvos miestams problemos ir uždaviniai, siekiant darniosios plėtros idealo, konstruktyvaus ir viešo planavimo proceso esamoje vertybių sistemos ir visuomenės intereso neapibrėžtumo situacijoje. Nagrinėjama, kokiuose bendrojo planavimo etapuose tikslinga remtis ekspertinio vertinimo rezultatais, ir analizuojamas šių rezultatų pritaikomumas. Straipsnyje pateikti ekspertinių vertinimų rezultatų tyrimai Lietuvos miestų teritorijų planavimo darbe iki šiol netaikyti praktikoje.Reikšminiai žodžiai: darnioji plėtra, teritorijų planavimas, bendrasis planas, ekspertiniai vertinimai, visuomenės vertybės, nuomonių suderinamumas ir priklausomybė nuo socialinių bei ekonominių veiksnių.First published online: 21 May 2013